Trade costs, trade balances and current accounts : an application of gravity to multilateral trade - Giorgio Fazio; Ronald MacDonald; Jacques Melitz (Center for Economic Studies and ifo Institute (CESifo), 2005)
In this paper we test the well-known hypothesis of Obstfeld and Rogoff (2000) that trade costs are the key to explaining the so-called Feldstein-Horioka puzzle. Using a gravity framework in an intertemporal context, we provide strong support for the hypothesis and we reconcile our results with the so-called home bias puzzle. Interestingly, this requires a fundamental revision of Obstfeld and Rogoff's argument. A further novelty of our work is in tying bilateral trade behavior to desired aggregate trade balances and desired intertemporal trade.
Keywords: F32; F10; 330; Feldstein-Horioka puzzle; trade costs; gravity model; home bias puzzle; current account; trade balance; Sparen; Investition; Internationale Kapitalmobilität; Außenwirtschaft; Transaktionskosten; Transportkosten; Schätzung; Gravitationsmodell; Welt